Intraosseous access in neonates is feasible and safe – An analysis of a prospective nationwide surveillance study in Germany - Schwindt, Eva; Pfeiffer, Daniel; Gomes, Delphina; Brenner, Sebastian; Schwindt, Jens-Christian; Hoffmann, Florian; Olivieri, Martin (Frontiers in Pediatrics, 2022)
Background: This was a prospective surveillance study to investigate reports on the safety and frequency of use of intraosseous (IO) access in neonates. Methods: Over a two-year period, paediatric hospitals in Germany were asked to report all cases of IO access to the nationwide Surveillance Unit for Rare Paediatric Diseases (ESPED). Hospitals reporting a case submitted responses via an anonymized electronic questionnaire, providing details on indication, success rate, system used, location, duration to first successful IO access, complications, alternative access attempts and short-term outcome. We present a subset of data for IO use in infants of less than 28 days. Results: A total of 161 neonates (145 term and 16 preterm born infants) with 206 IO access attempts were reported. In 146 neonates (91%), IO access was successfully established, and success was achieved with the first attempt in 109 neonates (75%). There was no significant impact of gestational age or provider’s educational level on success rates. In 71 infants with successful IO access (79%), the estimated duration of placement was less than three minutes. The proximal tibia was the predominant site used. A semiautomatic battery-driven device was used in 162 attempts (88%). The most often applied medications via IO access were crystalloid fluid and adrenaline. Severe complications occurred in 9 patients (6%). Conclusion: Within this surveillance study, IO access in neonates was feasible and safe. IO access is an important alternative for vascular access in neonates.